New realities, new goals - Abd Razak, Dzulkifli (2005)
THE University of Malaya celebrates its centennial anniversary this year. This is significant not only for Malaysia's oldest university but also for the country's higher, education, which is older than the history of independent MalayaMalaysia. Just as it turned 100, UM became one of two local universities listed among the top 200 world's best, according to the reputable The Times' Higher Education Supplement (THES) 2004. The other is Universiti Sains Malaysia (USM), the second oldest university in Malaysia which, at 35 years old, is distinctly among the youngest to be listed. Among Asian universities, UM is ranked 13th and USM 15th, compared to the 32nd and 57th ranking by the Asiaweek magazine (now defunct) in 2000. This is certainly a vast improvement in a short period of four years.